An exploration of factors that have facilitated and constrained access, adoption and availability of mind-body therapies as adjunctive interventions to treat trauma-related conditions in Aotearoa, New Zealand : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University - Te Kunenga ki Pūrehuroa, Albany, Aotearoa New Zealand - Standing, Meredith (Massey University, 2025)
This qualitative study explores factors that facilitate and constrain the use of mind-body interventions to treat trauma-related conditions in Aotearoa New Zealand (NZ). The phenomenon explored references mind-body therapies as an adjunctive treatment option with a focus on trauma-sensitive yoga. This study is intended to examine mind-body interventions as a complementary treatment approach and augmentation of interventions such as cognitive behavioural therapies and other validated, evidence-based approaches to treating trauma-related conditions. There is a significant body of literature that supports the use of talk therapies, such as cognitive behavioural therapy, to treat symptoms associated with trauma-related mental health conditions. Recent research has revealed that in many cases, trauma cannot be resolved through interventions that utilise talk therapies alone, as trauma, according to some theorists, is located not only in the core of the brain but also within the body. A practical treatment approach to mitigate individual experiences of trauma is to integrate Western psychological talk therapy approaches with those that focus on calming the nervous system, such as trauma-sensitive yoga, romiromi, mindfulness, and somatic experiencing. The current study highlights factors across the social system that have facilitated and constrained the access, adoption, and availability of mind-body therapies as complementary approaches for treating trauma-related conditions in the NZ context. Findings in the current study highlight that in the NZ context, few factors have facilitated access, adoption and availability of mind-body therapies as adjunctive interventions to treat trauma-related mental health conditions. A more significant number of factors, it appears, have constrained access, adoption and availability of mind-body therapies. Findings illuminate an overall positive attitude toward the utility of mind-body therapies as adjunctive treatments for trauma-related conditions, which highlights the potential for greater use of such interventions in the NZ setting.
Keywords: trauma, interventions, Aotearoa New Zealand, psychology, cognitive behavioural therapy, complementary therapy, mind-body, complementary and alternative medicine, integrative medicine, trauma-sensitive yoga, trauma centre trauma-sensitive yoga, traditional healing, Indigenous populations; Psychic trauma; Patients; Care; New Zealand; Post-traumatic stress disorder; Alternative treatment; Body-mind centering; 520302 Clinical psychology